Vascular endothelial cells on two-and three-dimensional fibrin assemblies for biomaterial coatings - Filová, Elena; Brynda, Eduard; Riedel, Tomás; Bacáková, Lucie; Chlupác, Jaroslav; Lisá, Vera; Houska, Milan; Dyr, Jan E (Journal of biomedical materials research. Part A, 2009)
Various techniques for coating synthetic surfaces with fibrin structures were tested for seeding bovine pulmonary artery endothelial cells (EC). Two-dimensional fibrin (Fb) structures (2D Fb) were obtained by successively repeating adsorption of fibrinogen (Fbg), incubating the surface with thrombin (Thr) solution, and inhibiting surface-attached Thr. Three-dimensional fibrin networks immobilized at the surface (3D Fb) were formed by catalytic action of surface-attached thrombin on an ambient Fbg solution. Ultra-thin 3D Fbs were obtained if thrombin inhibitors antithrombin III and heparin were added into an Fbg solution. The formation of surface fibrin structures was observed in situ using surface plasmon resonance. The morphology of the structures was studied by transmission and scanning electron microscopy. A polylactide fibrous scaffold was modified with a surface fibrin film without filling the inner pores with a bulk gel. The growth of EC seeded on a polystyrene surface coated with the Fb films was evaluated by the number and morphology of the adhering ECs and the concentration of beta-actin, vinculin, alpha(v)-intergrin, and von Willebrand factor (vWF). The best initial cell spreading after 1 day was observed on 2D Fb and ultra-thin 3D Fb. The highest concentration of vWF, a marker of EC differentiation, was observed after 3 days on thick 3D Fbs. The highest EC population densities after 7 days were observed on 2D Fb and thick 3D Fb.
Keywords: Gels; Cattle; Heparin; povrchové vlastnosti; Actins; Adsorption; Endothelial Cells; endoteliální buňky; testování materiálů; Materials Testing; skot; buněčné kultury; Vinculin; integrin alfaV; Antithrombin III; trombin; aktiny; antithrombin III; adsorpce; von Willebrandův faktor; von Willebrand Factor; Integrin alphaV; kultivované buňky; vinkulin; biokompatibilní potahované materiály; Coated Materials, Biocompatible; Animals; fibrin; lidé; Thrombin; Humans; zvířata; Cell Culture Techniques; Surface Properties; Tissue Scaffolds; Cells, Cultured; Fibrin; Polyesters; gely; fibrinogen; tkáňové podpůrné struktury; Fibrinogen; heparin; polyestery